Peran Negara untuk Mewujudkan Kesejahteraan dalam Kerangka Maqashidus Syariah - Mulyana, Rijal Assidiq (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
The research was conducted to explain the role of the State in realizing welfare within the framework of maqashidasysyariah. maqashidasysyariah is a view developed by al-Ghazali to explain and accommodate the purposes of the Sharia. Al Ghazali mentions that a welfare society is a society that can meet the needs of its dien, its nafs, its aql (its intellectual needs), nasl (descendant), and maal (wealth). In various literature studies, the authors found that only an Islamic State can realize such welfare and not in the form of another State. The welfare is mobilized into an institutional role as follows the non-material welfare of accommodating the needs of the community for its worship and the physical well-being of society as its basic physical needs are accommodated in political and economic activity.